Functional strategies in gilthead seabream (Sparus aurata) juvenile nutrition: dietary microalgae supplementation for higher resilience - Gonçalves, Pedro Miguel da Conceição (2024)
Gilthead seabream (Sparus aurata), a species of high commercial value, often faces stressors inherent to aquaculture practices, which can negatively affect health, leading to diseases and economic losses. Given the pivotal role of nutrition in addressing such challenges, this study aimed to evaluate the effects of Tetraselmis chui extracts as functional dietary supplements to enhance fish resilience during acute stress events. A feeding trial was performed in juvenile gilthead seabream where three dietary treatments were tested in triplicate: CTRL – commercial-like diet; LOW – commercial-like diet supplemented with 0.06 % of T. chui extract; and HIGH – commercial-like diet supplemented with 0.12 % of T. chui extract. Fish were randomly distributed among 9 tanks (n = 20 fish per tank). After three weeks of feeding, growth performance indicators and oxidative status biomarkers were assessed. Fish were then exposed to various stressors and tissue samples were collected 6 h post-challenge to evaluate antioxidant responses. Oxidative status was assessed by measuring lipid peroxidation, total antioxidant status, catalase activity and total glutathione content in liver before and after the challenge. Results showed that fish fed the LOW diet significantly improved total antioxidant status after stress. Additionally, lipid peroxidation levels between pre- and post-stress events were significantly lower in the LOW and HIGH treatments compared to the control. While no significant differences were found in the remaining biomarkers, trends indicated beneficial effects in LOW and HIGH fish. This indicates that the beneficial effects are mostly observed in the LOW treatment. LOW fish exhibit less variation in LPO before and after the challenge, and significantly higher total antioxidant capacity 6 h after the stress events. The HIGH fish showed either no beneficial effects or only minimal effects. In conclusion, the 0.06 % microalgal supplementation increased stress resilience in gilthead seabream.